(De)localization of Arbitration - Online vs. Offline Arbitration - E-arbitration in time of Covid 19 - Deskoski, Toni; Dokovski, Vangel; Kocev, Ljuben (Faculty of Law Iustinianus Primus, 2021)
“We are living in unprecedented times” - a statement in all aspects of our lives for the past year. This is also valid for international commercial arbitration. Like never before COVID 19 is changing and reshaping the world of arbitration. From expensive places for arbitral hearings to online platforms, from in-person hearings to virtual hearings. The direct impact of the lack of universal lex arbitri can be observed in the field of online and offline arbitration. In this sense, the terms “online” and “offline” arbitration are used to demonstrate the difference between in-person and virtual conduct of the arbitration. Traditional arbitration is converting into e-arbitration. By doing so, many national legislators and arbitral institutions are modernizing their rules just to provide an appropriate framework for e-arbitration. However, some of the theoretical concepts are more vivid now than before. The detach of international arbitration as a concept in the arbitration theory once again is attracting the attention of many legal scholars. Adapt, improve, and overcome – is the new standard in international arbitration. And this standard needs to fit with the basic principle of international commercial arbitration – due process and right to be heard.
Keywords: e-arbitration, lex arbitri, delocalization, seat of arbitration.